Na-TiNT Nanocrystals: Synthesis, Characterization, and Antibacterial Properties - Enzo V. H. Agressott; Mauro M. Oliveira; Thiago S. Freitas; Raimundo L. S. Pereira; Ana R. P. Silva; Rafael P. Cruz; Antonia T. L. Santos; Alexandre M. R. Teixeira; Tainara G. Oliveira; João H. da Silva; Alexandre R. Paschoal; Bartolomeu C. Viana; et al. (Bioinorganic Chemistry and Applications)
Titanium nanotubes have attractive morphological and physicochemical properties for several applications, such as high surface area, mesoporous structure, good stability, ion exchange capacity, and antibacterial property. Therefore, the field of nanotube applications is increasingly expanding, such as in solar cells sensitized by dye, photocatalysis, and antibacterial activity, among others. Therefore, a study of the antibacterial properties of sodium titanate nanotubes (Na-TiNTs) was carried out together with physicochemical characterizations, such as Raman spectroscopy which shows a peak characteristic of Na-O-Ti from nanotube-agglomerated regions. The XRD diffractogram confirmed the Raman spectra and evidenced the crystalline structure associated to Na-TiNT, which showed the characteristic peaks of the sodium trititanate crystal. SEM and TEM images showed the morphology of hollow nanotubes and forming semispherical particles. EDS shows the percentage values of each of the compounds in the Na-TiNT. The bacterial activity of the Na-TiNT was analyzed in Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. Na-TiNT modified the activity of the gentamicin and norfloxacin antibiotics against multiresistant strains. Synergistic effects against Gram-positive S. aureus 10 and Gram-negative P. aeruginosa 15 bacteria were observed when the Na-TiNT was associated with gentamicin, reducing the concentration of this antibiotic that is required to inhibit bacterial growth. Another synergic effect was observed for S. aureus 10 with norfloxacin.